2005
DOI: 10.1179/136485905x51436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climatic, socio–economic and behavioural factors on the transmission of hookworm (Necator americanus) on two low-country plantations in Sri Lanka

Abstract: The climatic, socio-economic and behavioural factors influencing hookworm (Necator americanus) infection in Sri Lanka were explored between February 2000 and June 2001. In February 2000, a single stool sample was collected from each of the 477 subjects investigated, who were aged 2-74 years (median = 13 years) and lived on the 'lowcountry' Maliboda and Ayr plantations. The 'baseline' prevalence (28.5%) and intensity of hookworm infection (0- 4828.5 eggs/g faeces, with a mean of 128.4 eggs/g) were then determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…17,24,[35][36][37] The current study found WASH impacts on the prevalence of A. lumbricoides to other intervention trials of household-and school-based hygiene promotion programs that have shown a reduction in A. lumbricoides reinfection on primary school-age children. 38,39 In Brazil, Moraes and colleagues 40 found great reductions in the prevalence of infection because of community sanitation improvement.…”
Section: Discussionmentioning
confidence: 80%
“…17,24,[35][36][37] The current study found WASH impacts on the prevalence of A. lumbricoides to other intervention trials of household-and school-based hygiene promotion programs that have shown a reduction in A. lumbricoides reinfection on primary school-age children. 38,39 In Brazil, Moraes and colleagues 40 found great reductions in the prevalence of infection because of community sanitation improvement.…”
Section: Discussionmentioning
confidence: 80%
“…Again, since albendazole which was offered at admission is efficacious to hookworms, the observed high prevalence hookworm infection in our study may signify infections acquired after admission. This correlates with documented risk factors which are common among patients admitted to psychiatric hospitals such as poor personal hygiene [ 33 36 ], poor sanitation [ 34 , 37 ], and exposure to soil with filariform larvae that penetrate the skin [ 35 , 38 , 39 ]. Psychiatric patients in the study site tend to walk around bare-footed, the majority of them with poor personal care including poor defecation practices which are the common risks for hookworm infection [ 25 – 29 ].…”
Section: Discussionmentioning
confidence: 92%
“…Acquiring hookworm infection is directly related to exposure to soil where filariform larvae, the infective stage, live in and penetrate human skin. 4,15,16 Poor personal hygiene, particularly defecation practices [16][17][18][19] and sanitation, 17,20 have been reported as risk factors of hookworm infection. Hookworm infection has been associated with low socioeconomic status 16 and low educational attainment.…”
Section: Discussionmentioning
confidence: 99%